Geological Analysis and Model Test of Bedding Rock Cutting Landslide - Tian-Wen Lai; Zhi-Yang Ji; Hong-Gang Wu; Shao-Long Zhang; Hao Lei; Yu Liang (Advances in Civil Engineering)
To explore the staged catastrophic evolution mechanism and failure process of bedding rock landslides under construction disturbance and rainfall conditions, we selected water content, displacement, strain, and soil stress as the study objects and carried out a model test. Combining the test phenomena, the following conclusions are drawn: first, bedding rock landslides have experienced three different stages of initial, constant velocity, and accelerated deformation affected by construction and rainfall factors. Then, the mode of bedding rock landslides is both sliding and traction sliding compound sliding mode. Finally, in the initial and constant deformation stages, the stress and strain values in the soil both increase slightly. In the accelerated deformation stage, the horizontal and vertical deformation at the slope foot increases sharply. Meanwhile, the strain value increases greatly, the stress decreases, and the stress in the slope increases significantly. Therefore, stress, strain, and displacement can be used as early warning indicators for staged disasters of bedding rock landslides.